Mystic doubt: In search of pure consciousness - Ohlson, Olof (Anthropology of consciousness, 2025)
Transcendental Meditation (TM) holds that the essence of reality is "pure consciousness." This piece contrasts three interpretations of their meditative trance: (i) TM doctrine, and (ii) scientific physicalism, (iii) with my own meditative experience. Pure consciousness events, defined as wakeful contentless consciousness, are known to occur, but what ontological basis do they have? While cosmic consciousness may be the only ontological ultimate there is, my meditative introspection does not neatly align with TM dogma. In search of the right metaphor, this piece journeys over mystical notions of divine darkness, contemplates evidence regimes, and proposes "mystic doubt" or ontological skepticism as an alternative to ontological relativism.